PARAMETRIC ANALYSES OF AN ABSORPTION REFRIGERATION SYSTEM WITH WATER AND LITHIUM BROMIDE IN STEADY STATE POWERED BY SOLAR ENERGY - Prendin, V.; Martinez, L. C.; Kaminari, N. M. S. (Revista de Engenharia Térmica, 2022)
The demand of energy utilization is increasing expressively as fast as the development of countries. Besides being available everywhere and virtual inexhaustible, renewable energy is undoubtedly necessary to avoid depleting the planet’s natural resources and global warming. Even considering the primordially environmental importance, the result of no emissions by renewable energy grant attractive also for political and economics statement. It should be noted the sun is the most abundant primary energy source in the planet and essential for eco-friendly process like photosynthesis, wind action, water cycle as well direct uses as electric and thermal generations. Consequently, nowadays several methodologies have been applied in order to transfer energy between the cycle and its surroundings optimizing for instance the coefficient of performance and heat exchangers. An absorption system is widely applied in these cases due to supply a unique solution for a range of technological problems from solar cooling to steam-driven refrigeration. Alternatively, this article main objective is modulating an absorption refrigeration system (ARS) which uses water-lithium bromide as a working fluid. Therefore, using the software Engineering Equation Solver (EES) is possible to obtain a thermodynamic single effect code that allows elaborating parametric analyses. In other words, performed and verified the influence of some input parameters over other output parameters. First, it was necessary to consider the cycle operating as reversible and steady state. Furthermore, it is assumed that no chemical reactions occur between water and lithium bromide. Thus, in the meantime apply the heat exchangers and a Solar Collector to receive the thermal energy and provide to the refrigeration cycle. Similarly, water from external sources was used to change heat with the fluid water-lithium bromide. Satisfactory results were founded and it enable to calculate and evaluate all system heat transfers rates and coefficient of performance. Almost all of input parameters introduced brought adequate values over output parameters, but the most convenient were: mass balance of water-lithium bromide solution and temperature of cold water from outside source. Clearly, results always can be found but in conclusion this article can be used to verify parameters sensitivity, optimized absorption refrigeration solutions and supply knowledge for future applications.